Effectiveness of physical exercise programs on cardiorespiratory responses in women during pregnancy and postpartum (Research, Society and Development, 2022)
The physiological changes that occur during the life of women during pregnancy and postpartum are already well evidenced in the scientific literature. It is known that the practice of physical activity can be an important protective factor against the conditions observed in these milestones in women's health. The objective of this study was to discuss the effectiveness of physical exercise programs on cardiorespiratory responses in women during pregnancy and postpartum period. This is a literature review. The search consisted of the Scientific Electronic Library Online (SciELO) and the Latin American and Caribbean Center for Health Sciences Information (Bireme). The articles were selected based on the following keywords in Portuguese: strength exercise, pregnancy, postpartum. Only articles published from 2012 to 2020, literature review studies and only in Portuguese and English were selected. In total, 7 studies were part of this review. Cardiorespiratory improvements due to physical exercise are positive for pregnant women as it contributes to the health of women and babies, as well as cardiorespiratory improvements for women in the postpartum phase, considering the particularities of this milestone, reducing health problems in the maternity. The need for health professionals, in particular physical education professionals, to seek knowledge about the prescriptions, guidelines and contraindications in performing physical activity for this population is highlighted, so that the intervention is carried out effectively and safely, ensuring health of the woman.